Goal Attainment Scaling for haemophilia (GAS‐Hēm): testing the feasibility of a new patient‐centric outcome measure in people with haemophilia. Issue 4 (6th April 2018) - Roberts, J. C.; Lattimore, S.; Recht, M.; Jackson, S.; Gue, D.; Squire, S.; Robinson, K. S.; Price, V.; Denne, M.; Richardson, S.; Rockwood, K.
Abstract : Introduction: To address the need for a patient‐reported outcome that can measure clinically and personally meaningful change in people with haemophilia (PwH) on prophylaxis, an approach based on Goal Attainment Scaling (GAS) was developed: the GAS‐Hēm. Aim: To establish real‐world feasibility of GAS‐Hēm in PwH. Methods: Patients aged 5‐65 years were enroled from four North American centres for a 12‐week study. The primary outcome was the proportion of participants who completed GAS‐Hēm interviews at baseline, 6 and 12 weeks. GAS‐Hēm scores were obtained by subject‐ and clinician‐rated goal attainment at Weeks 6 and 12, and compared with quality of life (QoL) measures and annualized bleed rate (ABR) for construct validity. Goals were evaluated qualitatively for content validity. Responsiveness was calculated using standardized response means (SRM). Results: Forty‐two participants set 63 goals. Participants preferred to define (37/63) their own goals or further individualize (23/63) from the GAS‐Hēm menu. Thirty of the 37 self‐defined goals were matched to goals on the GAS‐Hēm menu. The most common goal areas were: weight, exercise and nutrition (n = 17); leisure activities (n = 8); and joint problems (n = 7). Both participant‐ and clinician‐rated GAS‐Hēm scores at 6 weeks (n = 40) and 12 weeks (n = 41) demonstrated satisfactory goal attainment (SRM [subject‐rated] at 12 weeks for adult and paediatric groups was 1.25 and 1.16, respectively). Correlations of GAS‐Hēm scores with QoL measures and ABR were uniformly small. Conclusion: GAS‐Hēm was feasible and tapped constructs not captured by ABR or QoL measures.